Construction and Validation of a Scale to Measure Quality of Life for Youth in Jordan - Al-Khayat, Majed; AL-Adwan, Fatima (Dirasat: Human and Social Sciences, 2019)
This study aimed to construct a scale to measure QOL for youth in Jordan. The study sample consisted of (630) university students (Males and Females) that are enrolled in scientific and humanitarian specializations at both of University of Jordan and Al-Balqa Applied University. The researchers developed a scale to measure QOL, which includes (43) items; categorized based on (7) dimensions (emotional life, social life, family life and habitat, public health and daily jobs, luxury, religious life, and technological facilities). The results revealed that there are statistical differences of QOL according to gender and resident place variables while statistical differences of QOL for the university specialization variable.